Digital divide and women’s (dis)empowerment: A study of selected tribal communities in the Wayanad District of Kerala, India - Arya, S; Pradeep Kumar, B (Journal of Telecommunications and the Digital Economy, 2025)
This study explores digital empowerment among tribal women in Wayanad, Kerala, India, where remote communities are often disconnected from mainstream society and lack digital access. Using probability proportionate to size sampling and statistical methods like Chi-Square and Random Forest, it found many tribal women are digitally disempowered, with no access to the internet or social media. Notably, women from the Paniya and Adiya communities, among the most marginalised, are particularly disadvantaged. The digital divide hinders their empowerment, calling for targeted government efforts to address this issue, essential for their social and economic upliftment in the digital age.